2012
DOI: 10.3136/fstr.18.183
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Enumeration of Microbial Cells in Solubilized Soymilk Using an Automatic Cell Counting System with LED Illumination

Abstract: A fluorescent filter method using the Bioplorer apparatus and a conventional standard plate count method were compared for microbial cell enumeration in soymilk. Soymilk samples were solubilized for filtration. The microbial cell count obtained using the Bioplorer method showed good correlation with that obtained by the standard plate count method. The results of this study showed that the Bioplorer method is a rapid and efficient method for enumeration of bacterial cells in soymilk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Figure 1. Schematic of the LED-illuminated detection apparatus Tsumura and Tsuboi (2012) demonstrated that the total bacterial cells in solubilized soymilk could be enumerated using the automated cell counting system. However, for accurate viable cell count, the separation of microorganisms from the complex food matrix is essential (Araki et al, 2010;Benoit & Donahue, 2003;Fukushima et al, 2007;Stevens & Jaykus, 2004).…”
Section: Automated Microbial Cell Counting System With Fluorescent Staining In Processed Soy Foodsmentioning
confidence: 99%
“…Figure 1. Schematic of the LED-illuminated detection apparatus Tsumura and Tsuboi (2012) demonstrated that the total bacterial cells in solubilized soymilk could be enumerated using the automated cell counting system. However, for accurate viable cell count, the separation of microorganisms from the complex food matrix is essential (Araki et al, 2010;Benoit & Donahue, 2003;Fukushima et al, 2007;Stevens & Jaykus, 2004).…”
Section: Automated Microbial Cell Counting System With Fluorescent Staining In Processed Soy Foodsmentioning
confidence: 99%
“…Thus, rapid identification of bacteria is as important as enumeration of bacteria (Katase and Tsumura, 2011;Tsumura and Tsuboi, 2012;Katase et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the bacterial species also play an important role in soybean food-borne illness and spoilage. Thus, quality and safety of processed soybean products is important (Katase & Tsumura, 2011;Tsumura & Tsuboi, 2012). Based on the ribosomal proteins profiles of different bacteria, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been demonstrated as a rapid and reliable method for bacterial identification (Lay, 2001;Mazzeo et al, 2006).…”
Section: Evaluation Of Matrix-assisted Laser Desorption/ionization Timentioning
confidence: 99%